2009
DOI: 10.1016/j.molbiopara.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phosphodiesterase-5 as a surface protein in the tegument of Schistosoma mansoni

Abstract: Schistosoma mansoni is a major causative agent of schistosomiasis, an important parasitic disease that constitutes a severe health problem in developing countries. Even though an effective treatment exists, it does not prevent re-infection and the development of an effective vaccine still remains the most desirable means of control for this disease. In this work we describe the cloning and characterization of a S. mansoni nucleotide pyrophosphatase/phosphosdiesterase type 5 (SmNPP-5), previously identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 46 publications
5
47
0
1
Order By: Relevance
“…This tegumental localization of SmNPP-5 has been reported by other research groups using proteomic approaches (7,33) and immunofluorescence localization (26); also, as noted earlier, phosphodiesterese activity in tegument-enriched fractions of on May 7, 2018 by guest http://iai.asm.org/ adult worms was previously reported (10,11,23,25). The localization of SmNPP-5 as determined using immunogold electron microscopy and reported here confirms and extends those data.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This tegumental localization of SmNPP-5 has been reported by other research groups using proteomic approaches (7,33) and immunofluorescence localization (26); also, as noted earlier, phosphodiesterese activity in tegument-enriched fractions of on May 7, 2018 by guest http://iai.asm.org/ adult worms was previously reported (10,11,23,25). The localization of SmNPP-5 as determined using immunogold electron microscopy and reported here confirms and extends those data.…”
Section: Discussionsupporting
confidence: 91%
“…We proposed earlier that tegumental phosphodiesterase may participate with other schistosome tegumental phosphatase homologs in the catabolism of extracellular nucleotides (5). However, sequence analysis of this tegumental enzyme shows that it clearly belongs to the pyrophosphatase/phosphosdiesterase-5 (NPP-5) family (26), and members of this family have not been reported to metabolize nucleotides (30,31). In agreement with this sequence analysis, in our unpublished work, we found that SmNPP-5-suppressed parasites, though impaired in their ability to cleave the synthetic substrate p-nitrophenyl 5Ј-dTMP, are not impaired in their ability to degrade exogenous ATP, ADP, or AMP (data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is suggested that the combined use of chemotherapy and vaccination is the basis for a novel, more versatile method to control schistosomiasis (Bergquist et al 2005). The identification of appropriate schistosome antigens which could reduce pathology and limit parasite transmission is particularly important in the case of schistosomiasis (Rofatto et al 2009). …”
Section: Introductionmentioning
confidence: 99%